Frekuensi Pertemuan Dewan Komisaris dan Komite Audit Terhadap Manajemen Laba Dengan Pendekatan Non-Discreationary Accruals - Siti Wafiqoh Maulidiyyah Nurul Ichsany; T. Husain (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This research aim to obtain empirical evidence about the practice of earnings management in use of corporate governance mechanism which consists of the frequency of board and audit committees meeting. This study uses measurements of earnings management with the non-discreationary accruals (NDA) approach introduced by Jones. The population of this study is sub-sectors companies in the construction and building in 2010-2016. The sampling technique uses a purposive method. The method of data analysis uses multiple regression analysis, the classical assumption test previously and followed by hypothesis testing. The results of this research indicate that the frequency of board meetings does not significantly influence on the earnings management, while the frequency of audit committee meetings has a negative effect on the earnings management.